2018
DOI: 10.1111/icad.12319
|View full text |Cite
|
Sign up to set email alerts
|

Egg‐laying traits reflect shifts in dragonfly assemblages in response to different amount of tropical forest cover

Abstract: Oviposition site selection by aquatic insects is usually influenced by both aquatic and terrestrial cues. Landscape changes (e.g. native vegetation loss) can affect the level of the reproductive success in aquatic insects, changing local species composition and richness. We investigate whether forest cover loss around streams influences the number of species with exophytic (species which lay eggs directly on the water surface), endophytic (species which lay their eggs directly into plant tissue), or epiphytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 71 publications
1
44
0
2
Order By: Relevance
“…**** Species found only in areas with riparian vegetation of over 50 m in width. Rodrigues et al 2016, Rodrigues et al 2018a, Calvão et al 2018. Our results showed that areas of veredas classified as VRP have different Odonata communities to those found in areas classified as VRA.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…**** Species found only in areas with riparian vegetation of over 50 m in width. Rodrigues et al 2016, Rodrigues et al 2018a, Calvão et al 2018. Our results showed that areas of veredas classified as VRP have different Odonata communities to those found in areas classified as VRA.…”
Section: Discussionmentioning
confidence: 57%
“…The dragonflies were collected between November 2014 and January 2015. A standardized collection effort was adopted in each sampled stretch, as used in other studies (Rodrigues et al 2016, Calvão et al 2018, Rodrigues et al 2018a. The sweeping method was used to collect the samples, with a 1-hour sampling effort performed by two collectors (total of two hours per point) on a 100-meter stretch.…”
Section: Sampling and Identificationmentioning
confidence: 99%
See 3 more Smart Citations